Analysis of lncRNA and mRNA Repertoires in Lung From BAFF-R-Deficient Pneumocystis-Infected Mice - Rong, Heng-Mo; Zhang, Chao; Rong, Guang-Sheng; Li, Ting; Qian, Xiao-Jun; Wang, Dong; Tong, Zhao-Hui (Frontiers in Immunology, 2022)
Background: Pneumocystis pneumonia (PCP) is a common medical issue in immunosuppressive patients. Increasing evidence supports that B cells may play an essential role in PCP individuals. The present study aims to integrate lncRNA and mRNA expression profiles and furtherly investigate the molecular function of mature B cells in PCP. Methods: The lung tissue of WT mice and B cell-activating factor receptor deficient (mature B cells deficiency, BAFF-R–/–) mice were harvested at 3 weeks after infected with pneumocystis. After total RNAs being extracted, transcriptome profiling was performed following the Illumina HiSeq 3000 protocol. lncRNA-targeted miRNAs pairs were predicted using the online databases. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene ontology (GO) enrichment pathways were analyzed to functionally annotate these differentially expressed genes (DEGs). Additionally, the immune-related lncRNA–miRNA–mRNA ceRNA network was subsequently performed. The quantitative real time PCR (RT-PCR) analysis were conducted to evaluate the lncRNA and mRNA expression profiles in WT-PCP mice and BAFF-R–/– PCP mice. Results: Compared with the control group, 166 mRNAs were observed to be aberrantly expressed (Fold change value≥2; P <0.05) in BAFF-R–/– PCP group, including 39 up-regulated and 127 down-regulated genes, while there were 69 lncRNAs differently expressed in BAFF-R–/– PCP group, including 15 up-regulated and 54 down-regulated genes. In addition, GO and KEGG pathway analysis showed that BAFF-R deficiency played an important role in the primary and adaptive immune responses in PCP. Furthermore, the lncRNA and mRNA co-expression network was established. We noted that in the core network of lncRNA-TF (transcription factors) pairs could be classified into the categories including infection and immunity pathways. Conclusion: In summary, in this study, we furtherly explored the role of mature B cells in the pathogenesis and progression of PCP and the data demonstrated that BAFF-R deficiency could play a significant role in immune regulation in PCP population.